2017
DOI: 10.21894/jopr.2017.2903.05
|View full text |Cite
|
Sign up to set email alerts
|

DIET PREFERENCES AND REPRODUCTION OF TRANSLOCATED BARN OWL, Tyto alba javanica IN CAPTIVITY

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Some studies show barn owls have an affinity to feed on smaller prey (e.g. Dickman et al, 1991; Rizuan et al , 2017) while other studies have reported a tendency to feed on larger prey (Derting & Cranford, 1989; Castro & Jaksic, 1995). Our analysis show that barn owls prefer medium-sized Norway rats (40 to 120g) in urban areas, a finding similarly reported by Gaunt et al (1997) and Hindmarch and Elliott (2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show barn owls have an affinity to feed on smaller prey (e.g. Dickman et al, 1991; Rizuan et al , 2017) while other studies have reported a tendency to feed on larger prey (Derting & Cranford, 1989; Castro & Jaksic, 1995). Our analysis show that barn owls prefer medium-sized Norway rats (40 to 120g) in urban areas, a finding similarly reported by Gaunt et al (1997) and Hindmarch and Elliott (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Its renowned role as an efficient small mammal predator has led to barn owls being introduced in various landscapes. Barn owls have been introduced in islands (Au & Swedberg, 1966; Emmerson & Ascani, 1985), agricultural areas (Hafidzi & Naim, 2003b; Rizuan et al, 2017) and semi-urban areas (Meyer, 2008) for the purpose of controlling pest rodent populations. Barn owls are also translocated as part of reintroduction programs for declining local barn owl populations (Meek et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the oil palm landscape may not be similar with that in the Peninsular, with varied different species of rats abound, the translocated owls have established well and been breeding successfully [83]. In Lahad Datu, Sabah, owl's translocation programme that started with ten pairs of owl in 2015 has grown to a population of more than 700 individuals [84,85].…”
Section: The Use Of Barn Owl For Rat Control In Oil Palmmentioning
confidence: 99%